Dari Silo Menuju Sinergi: Memotret Peluang Konvergensi Institusi Memori pada Warisan Tambang Batubara Ombilin Sawahlunto - Hendrawan, Muhammad Rosyihan (Universitas Andalas, 2024)
The utilization of technology is a crucial step in managing various objects, attributes, and properties of cultural heritage. Through the application of technology, efforts to document and disseminate information and knowledge related to cultural heritage can be significantly optimized. Similarly, the use of museums, which serve as miniatures of sites or existing objects, plays a pivotal role. This paper explores opportunities to support efforts in documenting and disseminating various pieces of information and knowledge about the Ombilin Coal Mining Heritage of Sawahlunto, particularly for visitors seeking a deeper understanding of the information embedded within this world heritage site.